2005
DOI: 10.1539/sangyoeisei.47.259
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Actual Situation of Community Industrial Physicians for Small and Medium-Sized Enterprises and Their Involvement in Community Occupational Health Services

Abstract: The subjects of this study were 405 Japan Medical Association authorized industrial physicians, Community Industrial Physicians (CIPs), who belonged to the Shinjuku, Nakano, and Suginami Words' regional medical associations in the jurisdiction of the Shinjuku Labor Standards Inspection Office. Between November and December, 2003, the CIPs were mailed a questionnaire requesting information about their affiliations and activities, and as indicators of their willingness to participate in Community Occupational He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The questionnaires were seven pages long and the volume of questions might have contributed to the reduced response rates. However, the response rates were equivalent with, or higher than, previous surveys on similar subjects 17 , 24) .…”
Section: Discussionsupporting
confidence: 55%
“…The questionnaires were seven pages long and the volume of questions might have contributed to the reduced response rates. However, the response rates were equivalent with, or higher than, previous surveys on similar subjects 17 , 24) .…”
Section: Discussionsupporting
confidence: 55%
“…When a questionnaires survey on OPs’ activities in SSEs was conducted, Terada et al (2005) succeeded to obtain a higher response from OPs at 37.5% that was achieved when the survey was conducted in cooperation with medical associations in the regions. Muto et al (1997) reported a similarly high response rate of 37.9% in a questionnaire survey on the methods to persuade high management to support OHS, but the respondents included non-MDs (such as occupational nurses and safety and health supervisors) and OPs accounted for 37%.…”
Section: Discussionmentioning
confidence: 99%
“…Low participation rates (38.6-46.7%) of physicians in OHS despite acquisition of certification as OPs have also been reported for other prefectures [20][21][22][23] . Terada et al 17) observed that only 94 (23%) physicians were active out of 405 private clinic-or hospital-based physicians who had registered as OPs in a labour standard inspection office in central Tokyo. The number of OPs registered by the Kyoto Medical Association as certified OPs represent 1,448 members of the Association 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the activities and job satisfaction of OPs have been published by several research groups [11][12][13][14][15][16][17][18][19] as well as by a number of regional occupational health promotion centers [20][21][22][23] . Nevertheless, there are no currently available reports on the difficulties experienced by private clinic-or hospital-based part-time OPs in their daily OHS or that evaluate the time spent by OPs in various OHS activities.…”
Section: Introductionmentioning
confidence: 99%